PENGARUH TERAPI MUSIK KLASIK TERHADAP TINGKAT KECEMASAN IBU HAMIL TRIMESTER III DALAM MENGHADAPI PERSALINAN DI WILAYAH KERJA PUSKESMAS SITIUNG I TAHUN 2025 - Siti Ainawati Mumtazah; Ningsih Saputri; Chyntia Maikallita (Ensiklopedia of Journal, 2025)
Anxiety is mood disorder characterized by deep and persistent feelings of fear or worry. Efforts to reduce anxiety through non-pharmacological measures include classical music therapy. The purpose of this study was to determine the effect of classical music therapy on the anxiety levels of third-trimester pregnant women facing childbirth in the Sitiung I Community Health Center Work Area. This study used a quantitative approach method with a one-group pretest-posttest design. The sampling technique used Purposive Sampling with a sample size of 10 respondents. The instrument used was the HARS questionnaire. The results showed a p-value of 0.000 (α 0.05), with an average anxiety score of 22.90 before and 16.10 after the intervention. These findings indicate that classical music therapy has a significant effect in reducing anxiety levels in third-trimester pregnant women. Classical music therapy can be an effective and easy-to-implement non-pharmacological alternative to help reduce anxiety before labor.Keywords: Pregnant Women, Anxiety, Classical Music Therapy, Third Trimester